Arquitetura da Informação em Portais de Institutos de Pesquisa em Saúde: Estudo de caso da ENSP/FIOCRUZ na estrutura e representação da Informação - Ferreira, Carlos Alberto (2016)
The information architecture as a field of knowledge, are analyzed in relation to the area of Information Science. The history of the conceptual development of the information architecture is presented, exploring in particular the usability of applications, interaction design and classification structures. Understanding that can be inferred is that the information architecture can be designed as an interdisciplinary field of Information Science. The fundamental principles of this subfield are applied in the case study of the Internet portal of a research institution in the area of health, the Oswaldo Cruz Foundation. They are checked its operation, its information structure, the nature of the adopted language, its navigability and its suitability to the portal users' information needs. The case study of the Oswaldo Cruz Foundation to corroborate their information structure properly follows the principles of information architecture.